The Strengthening the Authority of the Public Prosecutor as Dominus Litis an Integrated and Accountable Indonesian Criminal Justice System - Henok, Adrianus Herman; Panggabean, Mompang Lycurgus; Saragi, Paltiada (Kosmik Hukum, 2026)
In Indonesia’s criminal justice system, the Prosecutor’s Office holds the primary function as the Dominus Litis (Case Controller), which means the authority to determine whether a case should proceed to the prosecution stage lies entirely with the public prosecutor. As such, the Prosecutor’s Office is a key factor in ensuring the criminal justice process operates effectively, objectively, and in accordance with the principles of due process of law under the Integrated Criminal Justice System (ICJS). The objectives of this research are: (1) to analyses the concept of Dominus Litis in Indonesia’s criminal justice system and compare it with those of other countries, such as France and the Netherlands; and (2) to evaluate the effectiveness of the Prosecutor’s Office as Dominus Litis in Indonesian law enforcement practices, particularly in its relationship with police investigators under the Integrated Criminal Justice System. This research is a literature-based study employing a normative juridical approach with analytical descriptive characteristics. The conclusions of this research are: the Prosecutor’s Office is a key actor ensuring that the criminal justice process operates effectively, objectively, and in accordance with due process of law under the ICJS, and 4 (four) strategies to strengthen the Prosecutor’s role as Dominus Litis such as: enhancing the competency of human resources within the Prosecutor’s Office, strengthening the integrity and independence of the Prosecutor’s Office, strengthening transparency and accountability in the prosecution process and strengthening coordination with other law enforcement agencies.